(untitled) (Bangladesh Journal of Pharmacology, 2016)
In goal of searching new active compounds with important biological activities, a screening of several plants from salt-marsh region of Chebba-Tunisia had been realized. Three species had been selected: Calendula arvensis, Chenopodium murale and Nicotiana glauca. The organic extracts of different aerial parts of these plants (stems, leaves and flowers) displayed variable contents of total polyphenols (TPP) and total flavonoids (TF). Flowers acetone extract from N. glauca contained the higher quantity in TPP (264.8 ± 1.6 µg GA/mg), while stems dichloromethane extract exhibited the best TF content (49.8 ± 2.2 µg QE/mg). The important TPP and TF contents reflected a good anti-oxidant and antimicrobial activities. The best acetylcholinesterase inhibitory activity had been shown in the fractions obtained after extraction with low polarity solvents. Whence, a correlation of flavonoids contents with biological activities had been shown, while, there was no correlation with acetylcholinesterase inhibitory activity. Video Clip of Methodology: DPPH radical scavenging activity: 3 min Full Screen Alternate